2020
DOI: 10.1200/go.20.00068
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Medicaid Expansion on Black/White Breast Cancer Mortality Disparities: A Difference-in-Difference Analysis

Abstract: PURPOSE Medicaid expansion was designed to increase access to health care. Evidence is mixed, but theory and empirical data suggest that lower cost of care through greater access to insurance increases health care utilization and possibly improves the health of poor and sick populations. However, this major health policy has yet to be thoroughly investigated for its effect on health disparities. The current study is motivated by one of today’s most stark inequalities: the disparity in breast cancer mortality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…This may reflect either the existence of programs to ameliorate race-based survival disparities (e.g., mandatory insurance coverage), or more likely a lack of statistical power. Following Medicaid expansion, data from the Center for Disease Control and Prevention (CDC) was queried for survival disparities associated with race (13).…”
Section: Outcome Disparitiesmentioning
confidence: 99%
“…This may reflect either the existence of programs to ameliorate race-based survival disparities (e.g., mandatory insurance coverage), or more likely a lack of statistical power. Following Medicaid expansion, data from the Center for Disease Control and Prevention (CDC) was queried for survival disparities associated with race (13).…”
Section: Outcome Disparitiesmentioning
confidence: 99%
“…We believe that Semprini and Olopade's 1 study suffers a number of shortcomings. Their study represents a snapshot of a bird's eye view of the ACA Medicaid expansion landscape.…”
mentioning
confidence: 98%
“…We read the study by Semprini and Olopade 1 with great interest. In their difference-in-difference analysis of the impact of Medicaid expansion on Black and White breast cancer mortality, the authors found Black women to have a higher mortality rate than White women.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We appreciate Dr Chu et al 1 for their interest in our study evaluating Medicaid Expansion for its effect on Black and White breast cancer mortality gap. 2 Conducted in 2018, our study used state-level, CDC population data on breast cancer mortality rates to create a ratio, which measured the disparity in mortality between non-Hispanic Black and non-Hispanic White women. 3 Using a quasiexperimental design, we estimated the effect of Medicaid Expansion on this disparity.…”
mentioning
confidence: 99%